IDENTIFICATION OF PARAMPHISTOMUM SPP. INFECTING THE RUMEN AND RETICULUM OF BALI CATTLE BASED ON MORPHOMETRIC ANALYSIS - Putri Gunarso; Nyoman Adi Suratma; Ida Ayu Pasti Apsari (Buletin Veteriner Udayana, 2024)
Paramphistomum spp. is a parasite that commonly infects the digestive tract, particularly the rumen and reticulum, of livestock. Each type of Paramphistomum exhibits distinct morphological and morphometric characteristics. In Indonesia, three types of Paramphistomum have been identified: Paramphistomum cervi, Gastrotylax cruminifer, and Gigantocotyl exsplanatum. The aim of this thesis is to determine the morphometry of Paramphistomum spp. infecting Bali cattle slaughtered at the Pesanggaran Denpasar Slaughterhouse in Bali. The study utilized a Descriptive Observation method. Samples were collected, including 7 Paramphistomum spp. from each Bali cattle and a total of 10 infected Bali cattle. Specimens were stained with Aceto-Carmine and measurements were performed using Image Raster software. The morphometric results showed an average body length of 11.55 mm, body width of 3.22 mm, pharynx length of 1.10 mm, pharynx width of 0.69 mm, ventral sucker length of 1.38 mm, and ventral sucker width of 2.79 mm. These morphometric findings closely approximate those of Paramphistomum cervi. Further research on Paramphistomum spp. is necessary, particularly exploring various factors influencing the size of these parasites and their identification in other regions.